On communicative competence and intercultural understanding through the lens of the Japanese government-approved English language textbook - Gonja, Chika; Musaev, Talaibek (Penerbit Universiti Kebangsaan Malaysia, 2023)
It has been more than decades since English education in Japan started focusing on communicative competence. Textbooks and lessons in public schools are chosen based on a government-made Course of Study (Guideline). The Guideline puts emphasis on communicative competence and intercultural understanding in terms of English language education. The Government’s efforts to enact reform measures have failed, and the outcomes of various international assessments of Japanese English proficiencies are unsatisfactory. It implies that despite great effort the goal set by the Guideline has not been achieved yet. Students are motivated to learn English not for communication purposes but for test taking. This study examines a government-approved textbook for high school students’ required course from Sanseido Press to see how the Guideline’s objective is reflected in it. Since it is important to raise cultural awareness, this study tries to figure out how this textbook helps students understand other cultures. This study uses Alptekin’s model of intercultural communicative competence and analyses the content of this textbook. This model is best for figuring out what makes effective intercultural understanding for nonnative English learners, which requires knowing about different cultures and being able to use that knowledge appropriately in any situation. The findings revealed a clear bias towards Japanese cultures and US citizens. It is assumed that American English is considered an ideal model for English education in Japan. It is recommended that textbooks accept the concept of World Englishes, include a more diverse culture, and get nonnative speakers involved.